The Narcissus Myth in Óscar Campo’s Yo soy otro (2008): From the Mystery of Being to (Self-)Terrorist Violence - Cantillo Lucuara, Mayron Estefan (Amaltea. Revista de Mitocrítica, 2017)
In this article, I thoroughly analyse the postmodern refiguration of the Narcissus myth in the film Yo soy otro (2008), directed by Colombian filmmaker Óscar Campo. From a broad philosophical perspective informed by contemporary epistemologies on the post-metaphysical subject, I aim to demonstrate that the film appropriates the Greek ephebe’s tragic story and puts it in dialogue with the existential concerns that determine the contemporary self, acting as the causal factors behind its self-absorption, radical individualism, extreme liquidity, lack of transcendental referents, and self-destructive drives.